Evidence for the perioperative care of mastectomized women - Carla Monique Lopes Mourão; Cristina Maria Galvão; Anna Paula Sousa da Silva; Tiago Barreto de Castro e Silva; Míria Conceição Lavinas Santos; Ana Fátima Carvalho Fernandes (Universidade Federal do Ceará, 2014)
This study aimed to evaluate the evidence available in the literature about the perioperative care provided to women submitted to mastectomy. An integrative review of scientific literature conducted in MEDLINE, CINAHL, LILACS, and SciELO databases, published from 2000 to 2011, using the controlled descriptors: preoperative care; preoperative period; intraoperative care; intraoperative period; postoperative care; postoperative period; perioperative care; perioperative period; and mastectomy. The sample of this review consisted of seven articles. The evidence pointed as perioperative care of mastectomy the pharmacological management of pain in different surgical periods. Despite the difficulty in presenting a consensus of evidence for perioperative care of mastectomy, there was concern on the part of professionals to minimize/prevent pre-, intra- and post-operative pain. Nursing should be aware, both of the update of pharmacological treatments in pain management and the development of future research related to nursing care in the perioperative period of mastectomy.